Teaching Vocabulary through the Implementation of Game-Based Learning for Junior High School Students: The Teachers' Perceptions - Nurafrilia Anindya Dwirahmita (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This article aims at knowing the teachers’ perception toward the use of game-based learning in teaching vocabulary for junior high school students. The research design used in this study is descriptive qualitative. One teacher from each three types of junior high school in Malang; private, public, and Islamic junior high school participated in the semi-structured interview. The interview was conducted through online meetings using Google Meet app due to the COVID-19 pandemic. Twelve questions were delivered in Bahasa (Indonesian) to ease the participants to understand and answer it then it was transcript to collect the data. The findings of this study are teachers’ shared positive perception toward the use of game-based learning as vocabulary teaching media. They also agreed that game-based learning is worth to enhance students’ vocabulary since there are more advantages despite the challenges they faced. Keywords: Teaching vocabulary, Game-based learning, teachers’ perceptions